Evaluation of Soil Nail Slope Stability Using SLOPE/W and PLAXIS 2D Software - Hashim, Aidil Shahmi; Yusof, Mohd Fairus (Recent Trends in Civil Engineering and Built Environment, 2025)
One crucial factor in geotechnical engineering is slope stability. Certain specialized software can be used in the geotechnical field for performing slope stability assessments. Nevertheless, the outcomes produced by any type of software could be differ. Thus, the purpose of this study was to evaluate the slope stability findings produced by the SLOPE/W and PLAXIS 2D software. Investigations were conducted into the effects of changing the embankment height (4, 6, and 8 meters) and soil nail angle (0, 15, and 30 degrees). The findings demonstrate that, for both software, the safety factor results for soil slopes strengthened with soil nails are greater than 1. In every scenario, a soil nail inclination of 30° yielded the safest slope, with the maximum FOS value recorded at 3.243. However, based on FOS values of 0.953 and 0.862, the natural slopes at heights of 6 and 8 meters are unstable. In conclusion, the FOS findings obtained from using SLOPE/W and PLAXIS 2D software are quite similar.